(untitled) (Bangladesh Journal of Public Administration, 2024)
This research aims to examine the Long-Run (LR) and Short-Run (SR) impacts of foreign exchange earnings (FEE) from international tourists’ arrival in Bangladesh and identifies the barriers to inbound tourism so that the government can take the appropriate development plans or programmes for inbound tourism. This study is carried out using secondary as well as primary data and by deploying mixed methods. For qualitative data, a Key Informant Interview (KII) is deployed. This study’s quantitative method relies on econometric analysis. It includes the Augmented Dickey-Fuller (ADF) unit root test, the Johansen cointegration test, and the Vector Error Correction Model (VECM) using yearly data ranging from the period 1995 to 2019. According to the cointegration and causality test results, there is no SR causal relationship between FEE and the number of tourist arrivals. However, an LR causal relationship exists not only between the earnings from foreign exchange and tourist arrivals numbers but also with the earnings from foreign exchange and capital investment in travel and tourism and earnings from foreign exchange and government spending on travel and tourism services. The qualitative data show that poor infrastructure and security of tourist destinations, lack of visa facilitation, high accommodation costs and unprofessional inbound tour operators are the major barriers to inbound tourism in Bangladesh. The results of the study will provide the Bangladeshi government with valuable information for crafting improved tourism policies that would benefit the nation’s economy.